Investigating size and surface modification to optimise the delivery of nanodiamonds to brain glial cells - Manami Takahashi; Ayaka Takada; Chihiro Suzuki; Kiichi Kaminaga; Masaki Yoshioka; Mariko Handa; Jeff Kershaw; Hiroshi Abe; Takeshi Ohshima; Ryuji Igarashi; Hiroyuki Takuwa (Discover Nano)
Abstract Nanodiamonds (NDs) with nitrogen-vacancy (NV) defects have garnered attention as promising nano-quantum sensors due to their high photostability, low biotoxicity, and ability to measure intracellular parameters such as temperature, magnetic fields, and electric fields. While NDs have been extensively studied in in vitro systems, their application in vivo remains underdeveloped. Efficient delivery of NDs to specific cells within biological tissues remains a critical challenge for advancing their applications in the life sciences. In this study, we investigated the intracellular uptake of NDs by glial cells (microglia and astrocytes) in the brain. Twelve types of NDs, differing in size (50 nm, 150 nm, 250 nm, and 350 nm) and surface modification (COOH, HPG and HPG-COOH), were locally injected into the brain parenchyma of mice. The intracellular uptake of NDs was assessed using immunostaining and confocal microscopy. Microglia preferentially internalized HPG-modified NDs. HPG-modified NDs also exhibited high diffusivity, facilitating interactions with surrounding microglia and enhancing uptake efficiency. In contrast, COOH-modified NDs were more efficiently internalized by astrocytes than HPG-modified NDs. This suggests that COOH-modified NDs tend to remain at the local injection site, where inflammation induced by tissue damage may have enhanced the phagocytic activity of astrocytes. These findings demonstrate that the uptake characteristics of NDs differ by cell type. HPG-modified NDs, are optimal for microglia, while COOH-modified NDs, are more suitable for astrocytes. It is anticipated that the results of this study will act as an important guide for the use of NDs as nano-quantum sensors in living brain tissues.